Clinical characteristics, obstetric and perinatal outcome of Covid-19 infection in pregnant women - Rabia Jamil; Nusrat Shah; Sofia Butt; Tahira Shah; Sarah Kazi; Fouzia Perveen; Hossain, Nazli (Journal of the Pakistan Medical Association, 2022)
Objective: To determine clinical characteristics, obstetrics and perinatal outcome of coronavirus disease 2019 infection in pregnant women. Method: The cross-sectional study was conducted at the Department of Obstetrics and Gynaecology of the Ruth Pfau Civil Hospital, Karachi, and Dow University of Health Sciences, Karachi, from August 2020 to July 2021, and comprised pregnant women with suspicion of coronavirus disease 2019 infection, who underwent recommended testing, and were found to be positive. Oral swabs for the presence of infection were also taken from the neonate within 24 hours of delivery. Data was analysed using Stata 11. Results: There were 41 women with a mean age of 27±5 years, a mean gestational age of 35±3 weeks, and mean parity 1.2±1.01. Of them, 3(7.3%) women died. Medical complications found along with coronavirus disease 2019 infection were pregnancy-induced hypertension 2(4.8%), eclampsia 4(11%) and diabetes mellitus 2(4.8%). Fever was the most common symptom seen in 12(30%) women, followed by cough 7(20%) and shortness of breath 6(14%). Majority 32(82%) of the women underwent caesarean section. The most common maternal complication was postpartum haemorrhage 6(20%). Also, 36(86%) women required intensive care unit stay for a mean 5±9 days. Conclusion: Fever, followed by cough and breathlessness, were the most common clinical features. Most common maternal and foetal complication was postpartum haemorrhage and low birth weight, respectively. Key Words: COVID-19, Pregnancy, Maternal outcome, Perinatal, Outcome.